Recent Trends in Antisense Therapies for Duchenne Muscular Dystrophy - Harry Wilton-Clark; Toshifumi Yokota (MDPI AG, 2023)
Duchenne muscular dystrophy (DMD) is a debilitating and fatal genetic disease affecting 1/5000 boys globally, characterized by progressive muscle breakdown and eventual death, with an average lifespan in the mid-late twenties. While no cure yet exists for DMD, gene and antisense therapies have been heavily explored in recent years to better treat this disease. Four antisense therapies have received conditional FDA approval, and many more exist in varying stages of clinical trials. These upcoming therapies often utilize novel drug chemistries to address limitations of existing therapies, and their development could herald the next generation of antisense therapy. This review article aims to summarize the current state of development for antisense-based therapies for the treatment of Duchenne muscular dystrophy, exploring candidates designed for both exon skipping and gene knockdown.